The Influence of Green Product Awareness and Perceived Benefit on Green Purchase Intention with Green Attitude as Mediating Variable (Case Study: Fore Coffee Customers in Yogyakarta) - Maria oktaviani Jemian; Nonik Kusuma Ningrum; Bernadetta Diansepti Maharani (Dinasti Publisher, 2025)
This study aims to analyze the influence of green product awareness and perceived benefit on green purchase intention, with green attitude as a mediating variable, among Fore Coffee customers in Yogyakarta. This study uses a quantitative approach with 120 respondents and data analysis techniques using SPSS. The results of the study indicate that green product awareness and perceived benefits have a positive and significant effect on green purchase intention. Additionally, green product awareness and perceived benefits also have a positive and significant effect on green attitude. However, green attitude does not have a significant effect on green purchase intention.